Life At rashtrapati bhavan - Edited by Gopalakrishnan, Sudha; Chandra, Yashaswini (Ed.) (New Delhi Publications Division, Ministry of Information and Broadcasting, GOI, 2016)
Life at Rashtrapati Bhavan.
Keywords: Rashtrapati Bhavan